REDEFINING THE TEACHER’S ROLE IN THE AGE OF ARTIFICIAL INTELLIGENCE: A MIXED-METHODS STUDY ON PEDAGOGICAL ADAPTATION AND PROFESSIONAL IDENTITY - Botirova Zebo Xakimjon-qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The accelerating integration of artificial intelligence (AI) into education is transforming the nature of teaching and learning, prompting educators to reconsider their pedagogical roles and professional identities. As AI-driven tools increasingly influence instructional design, assessment, and classroom interaction, teachers are required to adapt to new modes of practice that balance technological innovation with human values. This study explores how educators perceive and negotiate these changes, focusing on the dynamics of pedagogical adaptation and the evolving sense of professional identity in AI-enhanced environments. Adopting a mixed-methods design, the research combines survey data from 120 secondary and higher-education teachers with qualitative interviews conducted with 15 participants across multiple disciplines. The findings reveal that while AI facilitates greater efficiency, differentiation, and data-informed instruction, it also generates anxiety about autonomy, expertise, and ethical responsibility. Teachers who conceptualize AI as a collaborative partner rather than a competing force tend to demonstrate higher adaptability and professional fulfillment. The study concludes that effective integration of AI requires sustained institutional support, critical digital literacy, and a redefinition of teaching as a profession grounded in creativity, mentorship, and ethical judgment.